Biosynthesis of α-pyrones - Schäberle, Till F. (Beilstein Journal of Organic Chemistry, 2016)
The α-pyrone moiety is a structural feature found in a huge variety of biologically active metabolites. In recent times new insights into additional biosynthetic mechanisms, yielding in such six-membered unsaturated ester ring residues have been obtained. The purpose of this mini-review is to give a brief overview of α-pyrones and the mechanisms forming the basis of their natural synthesis. Especially the chain interconnecting enzymes, showing homology to ketosynthases which catalyze Claisen-like condensation reactions, will be presented.
Keywords: α-pyrones; biological activity; interconnecting ketosynthases; natural product; polyketides